DEVELOPMENT OF A DIDACTIC SIMULATOR FOR WATER TREATMENT SYSTEMS - Cordeiro, Armando J. L.; Almeida, Miguel C. L.; Almeida, Maria G. V. B. (International Journal of Research -GRANTHAALAYAH, 2022)
This paper presents the implementation of a didactic simulator for industrial automation supported by a supervision system. As a result of this work, a solution based on a system of six reservoirs was developed, together with a supervision system that allows the simulator to be controlled and monitored through a Raspberry Pi with a touch screen display and an android application. The aim of this work is to develop a system that can be used by other undergraduate and master’s students of the electrical engineering course at ISEL, for them to deepen their knowledge in automation. It is also intended that the simulator be used in fairs, exhibitions, and open days to internal and external students at ISEL, showing some of the work that has been developed in the master’s degree in electrotechnical engineering, especially in the field of industrial automation.